The dynamic failure mechanism of a lithium-ion battery at different impact velocity. (October 2020) - Xi, Shoujun; Zhao, Qiancheng; Chang, Lijun; Huang, Xingyuan; Cai, Zhihua
Highlights: Lithium battery shear failure behavior was discovered. The simulation model can well predict the mechanical response of the battery. Parameter analysis shows that the battery has obvious dynamic enhancement effect. Abstract: With the widespread popularity of new energy vehicles, the safety of its core power source, lithium-ion batteries (LIBs), has increasing attention. However, most of its vehicle safety problems are caused by mechanical failure, but its dynamic failure mechanism is still not clear. Firstly, based on the experiment, a battery computational model for analyzing the mechanical response of the battery is established. Secondly, on the basis of this, the battery dynamic response analysis under the different conditions is carried out, and the factors such as the end cap and the state of charge (SOC) correlation of the battery are considered respectively, and the failure behavior under high-speed load is analyzed in detail. Finally, the model is validated according to the experimental results, and the parameter research is further carried out to predict the failure behavior of the battery under dynamic load. The related results can provide a reference for the safety design of the battery under the mechanical integrity framework.